Implementasi Metode Viola Jones Untuk Perancangan Sistem Pemantauan Tempat Parkir Berdasarkan Digital Image Processing - Tonggam Harado Wilson Sinaga; Sinar Sinurat (Forum Kerja Sama Penddikan Tinggi (FKPT), 2022)
Image processing is image processing, which aims to improve image quality so that it can be easily interpreted by humans or machines. Image processing techniques transform images into other images. Image processing can be used in various fields, one of which is in terms of accessing the parking lot using the viola jones method. Viola-Jones applies the Adaboost (adaptive boosting) algorithm which can improve detection performance. The process of monitoring available and empty parking spaces using the Viola-Jones method is to classify objects in the image based on some simple feature values. There are several reasons to use these features instead of doing the filter process directly. The most basic reason is that the feature is a feature-based operating system so it's much faster than a pixel-based system. The image classification process is based on the value of a feature. The output is in the form of information about vacant parking locations and occupied parking lots.